Structural analogues of schweinfurthin F: Probing the steric, electronic and hydrophobic properties of the D-ring substructure - Ulrich, Natalie C. (Bioorg Med Chem, 2010)
The natural tetracyclic schweinfurthins are potent and selective inhibitors of cell growth in the National Cancer Institute’s 60-cell line screen. An interest in determination of their cellular or molecular target has inspired our efforts to prepare both the natural products and analogues. In this paper, chemical synthesis of analogues modified in different olefinic positions, and preliminary results from studies of their biological activity, are reported.